Dynamika systemu informacyjnego w świetle zachowań zbiorowych - Unold, Jacek (The dynamics of an information system in light of the influence of collective behavior, 2005)
The article concentrates on the nature of a social subsystem of an information system. It analyzes the nature of information processes of collectivity within an IS and introduces a model of IS dynamics. The model is based on the assumption that a social subsystem of an information system works as a nonlinear dynamic system. The model of IS dynamics is verified on the indexes of the stock market. It arises from the basic assumption of the technical analysis of the markets, that is, the index chart reflects the play of demand and supply, which in turn represents the crowd sentiment on the market
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 158-173